Pregnancy Related Thyroidal Dysfunction and its Feto-Maternal Outcomes - Amna Kazi, Sidra Hameed, Farheen Fatima, Maham Waseem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To detect the thyroidal dysfunction during pregnancy and the related outcomes. Study Design: Prospective study. Place and duration of study: Department of Obstetrics & Gynaecology, S. Z. Hospital Lahore from 01-01-2021 to 30-06-2022 Methodology: One thousand pregnant women in third trimester were enrolled for thyroid function test and screening, analysis of TSH, free T3 and T4 level. Results: Only 30 (3%) was having thyroid dysfunction while the dysfunction was reported highest in the women within 29-38 years of age. Most of the cases suffering from thyroid dysfunction are suffering from the subclinical hypothyroid condition (43%). The reduction in Apgar score was observed up to almost 3.59 times in newborns of thyroid dysfunction women. The risk of preeclampsia and cesarean section was also significantly raised in thyroidal dysfunction women. Odds ratio for low birth weight was observed as 6.32 with a significant association with thyroid dysfunction in pregnancy. Conclusion: There are poor feto-maternal outcomes of thyroid dysfunction during pregnancy with 43% of the cases as having subclinical hypothyroidism. Key words: Pregnancy, Thyroid dysfunction, Feto-maternal outcome